Feelings of Annoyance and Spoken Anger Words in Couples' Everyday Lives: The Role of Family-of-Origin Aggression. Issue 6 (August 2021) - Han, Sohyun C.; Schacter, Hannah L.; Timmons, Adela C.; Kim, Yehsong; Sichko, Stassja; Pettit, Corey; Margolin, Gayla
Little is known about the words that romantic couples use during emotionally heightened moments such as when feeling annoyed with their partner. In the present study, young adult couples received mobile phones that audio-recorded 50% of their day and prompted hourly self-reports of partner-related annoyance. Actor–partner models tested within-person (hourly) and between-person (across the day) associations between feelings of annoyance and spoken anger words; furthermore, exposure to retrospectively assessed parent-to-child aggression (PCA) was examined as a moderator of these links. Men reporting more annoyance across the day as well as greater PCA used more overall anger words. For women, hourly anger words fluctuated in relation to men's annoyance; moreover, greater PCA strengthened the link between women's own hourly reported annoyance and anger words. Our findings highlight nuances in couples' communication of everyday relationship distress and point to the role of PCA in next-generation romantic relationships.